Educational Issues Facing Aboriginal Families in Rural Australia: A Case Study - Appleyard, Susan (The Australian Journal of Indigenous Education, 2002)
This paper will provide a detailed plan of how the Aboriginal community of Geraldton could plausibly go about correcting its educational problems. Such a correction could foreseeably result in the easing of much poverty and the associated ramifications. The success of this plan is entirely based on the cooperation of not only the schools and the parents, but will require the support of students (both Aboriginal and non Aboriginal), the Education Department (National, State and local levels), Non Government Organisations in Geraldton, school staff and the wider community.